Canopy management of scattered Prosopis cineraria (L.) trees for sustainable fodder production in agricultural landscape of arid and semi-arid regions - N, Saresh; Godara, Asu Singh; Meena, Dharmendra; Bijarnia, Arjun Lal; Kumar, Dileep (Indian Journal of Agroforestry, 2022)
The experiment was carried out on Prosopis cineraria (L.) trees scattered in the agriculture land scape of Agricultural Research Station, Keshwana, Jalore, Rajasthan. Aim was to standardise the lopping intensity for different girth class ofÂ  trees for sustainable fodder production.. Fresh and dry fodder weight was higher in T1 (100 %) than T2 and T3. Among girth class treatment the sequence was G3 > G2 and G1. The combination T1G1 resulted in significantly higher fresh and dry fodder yield for both the year. Such interaction was observed for the combination T1G3 and for T2G2 combination. Percent increase in fresh fodder yield T2G2 combination had highest i.e. 46 %, highest dry fodder yield was observed in combination in T1G1 (35 %). There is increased inclination in carrying capacity, in T1 (0.38), G3 (0.59), and T1G1 (0.12), T1G3 (0.84) and T2G2 (0.19) combinations which supported 61.61, 94.96, 19.13, 136.04 and 31.57 no. of goats ha-1. There is a significant increase in the feed capacity, higher increase was observed for G3 along with T1 & T2 combination. For girth class G2 with T2 & T1 was found to be 9.02Â  No. ha-1 for 2018-20. Girth class G1 with lopping intensity T1 combination was 6.98 & 3.63 No. ha-1 respectively. Dry fodder yield had significant positive correlation with fresh fodder weight, percent change in fresh fodder weight, percent change in dry fodder production, and fodder feed capacity and significant negative correlation for crown width. It is concluded that for girth class G2- medium and for G1 & G3- heavy intensity lopping should be adopted for higher fodder production, carrying capacity, feeding capacity in Prosopis cineraria trees existing in the scattered agricultural landscape of arid and semi-arid regions